2020
DOI: 10.1152/ajplung.00185.2019
|View full text |Cite
|
Sign up to set email alerts
|

cAMP signaling primes lung endothelial cells to activate caspase-1 during Pseudomonas aeruginosa infection

Abstract: Activation of the inflammasome-caspase-1 axis in lung endothelial cells is emerging as a novel arm of the innate immune response to pneumonia and sepsis caused by Pseudomonas aeruginosa. Increased levels of circulating autacoids are hallmarks of pneumonia and sepsis and induce physiological responses via cAMP signaling in targeted cells. However, it is unknown whether cAMP affects other functions, such as P. aeruginosa-induced caspase-1 activation. Herein, we describe the effects of cAMP signaling on caspase-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
(44 reference statements)
1
9
0
Order By: Relevance
“…The importance of ExoU in disrupting host responses directed by lung endothelial cells is an emerging field of interest [32,[36][37][38][39][40]. Our previous work has shown that P. aeruginosa infection of PMVECs induces activation of caspase-1-dependent inflammation [44,45]. Intriguingly, the present study strongly suggests ExoU elicits a specific pattern of caspase-1 activation in PMVECs.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…The importance of ExoU in disrupting host responses directed by lung endothelial cells is an emerging field of interest [32,[36][37][38][39][40]. Our previous work has shown that P. aeruginosa infection of PMVECs induces activation of caspase-1-dependent inflammation [44,45]. Intriguingly, the present study strongly suggests ExoU elicits a specific pattern of caspase-1 activation in PMVECs.…”
Section: Discussionsupporting
confidence: 67%
“…In innate immune cells such as macrophages, caspase-1 activation typically leads to its release to the extracellular milieu where it can be measured [69]. However, we recently demonstrated that P. aeruginosa infection of PMVECs triggers caspase-1 activation that can be measured with an intracellular staining and flow cytometry technique (FLICA) [45]. The data presented herein suggest that ExoU specifically elicits intracellular caspase-1 activation in PMVECs, and the effect is dependent on ExoU PLA 2 activity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations